2008
DOI: 10.1143/jjap.47.1469
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Growth of InAs on Glass and Plastic Film Substrates by Molecular-Beam Deposition

Abstract: InAs layers were deposited on glass substrates by molecular-beam deposition at substrate temperatures of 180 -240 C at As/ In beam equivalent pressure (BEP) ratios of 3 -30. X-ray diffraction (XRD) patterns indicated that the InAs layers are polycrystalline and are more preferentially textured in the (111) plane when deposited at higher temperatures and lower As/In BEP ratios. Room-temperature Hall effect measurement showed that the films deposited at an As/In BEP ratio of 30 exhibit n-type conduction with ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…27) The carrier concentration of all the samples is quite high. It is suggested that 25) the electron concentration of LT grown InAs layers are predominated by antisite As concentrations. At low growth temperature with excess As, it is relatively easier to replace In atom from the lattice and replace it with an As atom which then can act as a double donor, 28) increasing the n-type carrier concentration.…”
Section: Electrical Properties Of Inas Single Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…27) The carrier concentration of all the samples is quite high. It is suggested that 25) the electron concentration of LT grown InAs layers are predominated by antisite As concentrations. At low growth temperature with excess As, it is relatively easier to replace In atom from the lattice and replace it with an As atom which then can act as a double donor, 28) increasing the n-type carrier concentration.…”
Section: Electrical Properties Of Inas Single Layersmentioning
confidence: 99%
“…The promotion of smooth surface growth and preservation of an adequate rate of growth can both be accomplished by changing the V/III ratio within the ideal range. There is a few reports of MnAs growth on InAs, 24) LT growth of InAs on glass/plastic substrate 25) and MnAs/InAs/MnAs thin trilayer on GaAs(111)B, 26) but to the best of our knowledge, no papers have been published that specifically investigate MnAs/InAs/MnAs thick double heterostructure on GaAs(111)B for the purpose of vertical spin-FET application. This underscores the novelty and significance of the present study, as it seeks to contribute valuable insights and fill this critical void in scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…Although III-V semiconductors as device active layers have excellent electronic properties, such as high electron mobilities and velocities, deposition of high-quality III-V semiconductor thin layers on FS's is problematic due to the difficulties. In fact, an InAs layer of ∼ 1 µm thickness on FS's, which is low-temperature deposited and polycrystalline, exhibits electron mobility of ∼ 500 cm 2 /V-s [1]; this mobility, while being higher than those of the polycrystalline Si layers, is far lower than those of crystalline InAs layers. In order to realize high-quality III-V semiconductor thin layers on FS's, bonding method is promising because it does not involve the difficulties of the temperature limitation and the noncrystallinity of FS's.…”
Section: Introductionmentioning
confidence: 99%